(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Skull-base tumors (SBTs) of the middle and anterior fossae typically cause mass effect on the optic nerve/chiasm complex. The most common of these neoplasms are pituitary adenomas, meningiomas and craniopharyngiomas. Clinical manifestations of SBTs vary and depend on tumor involvement, nature of growth pattern, and rate of growth. Chiasmal compression is accompanied by a gradual decrease in visual acuity, bitemporal visual field defects and development of primary descending optic atrophy (OA). Purpose: To investigate neuro-ophthalmological symptoms in patients with SBTs. Material and Methods: This retrospective study included the records of 500 patients who received treatment for SBT and loss of visual acuity and/or visual fields at the Romodanov Neurosurgery Institute during the period from 2017 through 2019. Patients underwent clinical and neurological, eye, and otoneurological examination (a routine otoneurological examination with assessment of cranial nerve function). Results: In patients with pituitary adenoma, chiasmal syndrome most commonly was symmetric (63.8%), and developed either gradually or (in a stroke-like course of tumor progression) abruptly. In addition, it was accompanied by a symmetric loss of visual acuity (77.1%), visual field defects (89.8%) and development of OA (50.5%). In patients with sella turcica meningioma, chiasmal syndrome most commonly was markedly asymmetric (65.7%), and accompanied by mild loss of visual acuity and visual fields in one eye, and severe or very severe visual acuity loss, residual visual field and OA in the fellow eye, as well as a particular compression of the anterior chiasm. Patients with supradiaphragmatic craniopharyngiomas had various amounts of loss of visual acuity and/or visual fields, and, most commonly, symmetric chiasmal syndrome and bilateral optic atrophy. In addition, the posterior chiasm (especially, the papillomacular bundle) was affected, which was manifested by bitemporal central scotoma (33.3%). Conclusion: We identified ophthalmological features of disease course in various histologic types of skull-base tumors. Loss of visual acuity and/or visual fields was an early and major symptom in the clinical picture of disease.